1999
DOI: 10.1070/rm1999v054n01abeh000122
|View full text |Cite
|
Sign up to set email alerts
|

Wess-Zumino-Witten-Novikov theory, Knizhnik-Zamolodchikov equations, and Krichever-Novikov algebras

Abstract: Abstract. Elements of a global operator approach to the WZWN theory for compact Riemann surfaces of arbitrary genus g are given. Sheaves of representations of affine Krichever-Novikov algebras over a dense open subset of the moduli space of Riemann surfaces (respectively of smooth, projective complex curves) with N marked points are introduced. It is shown that the tangent space of the moduli space at an arbitrary moduli point is isomorphic to a certain subspace of the Krichever-Novikov vector field algebra gi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
67
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 40 publications
0
67
0
Order By: Relevance
“…See [28] for a global operator version, and [29] for a sheaf version. In passing to the boundary of the moduli space one obtains the limit objects which are defined over the normalization of curves of lower genus.…”
Section: Introductionmentioning
confidence: 99%
“…See [28] for a global operator version, and [29] for a sheaf version. In passing to the boundary of the moduli space one obtains the limit objects which are defined over the normalization of curves of lower genus.…”
Section: Introductionmentioning
confidence: 99%
“…We obtain families of algebras over the moduli space M g,K+1 of curves of genus g with K + 1 marked points, and we are exactly in the middle of the main subject of this article. In [36] and [37] it is shown that there exists a global operator description of WZWN models with the help of the Krichever Novikov objects at least over a dense open subset of the moduli space. The following is just a very rough outline.…”
Section: Introductionmentioning
confidence: 99%
“…Tsuchiya, Ueno, and Yamada [38] gave a sheaf version of WZWN models over the moduli space. In [36], [37] Schlichenmaier and Sheinman developed a global operator version. In this context of particular interest is the situation I = {P 1 , .…”
Section: Introductionmentioning
confidence: 99%
“…A fair amount of interesting and fundamental work has be done by Krichever, Novikov, Schlichenmaier, and Sheinman on the representation theory of these algebras. In particular Wess-ZuminoWitten-Novikov theory and analogues of the Knizhnik-Zamolodchikov equations are developed for these algebras (see the survey article [She05], and for example [SS99], [SS99], [She03], [Sch03a], [Sch03b], and [SS98]). …”
Section: Introductionmentioning
confidence: 99%